2019
DOI: 10.1155/2019/4204375
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone-Loaded Chitosan Beads Coated with a pH-Dependent Interpolymer Complex for Colon-Specific Drug Delivery

Abstract: Chitosan (CS) microparticles loaded with dexamethasone were prepared by spray drying, followed by coating with a pH-dependent interpolymer complex based on poly(acrylic acid)/poly(vinyl pyrrolidone) using an water-in-oil emulsion technique. The aim of this research was to evaluate the influence of PAA/PVP coating on the release of dexamethasone from loaded chitosan microparticles, in simulated gastric fluid (SGF, pH=1.2) and simulated intestinal fluid (SIF, pH=6.8). The release of dexamethasone from uncoated l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…A controlled release of the drug Dexamethasone from CS was observed once the coating layer of the pH-dependent polymer complex started to dissolve at a higher pH (6.8). It was concluded that the CS nanoparticles coated with PAA-PVP complexes can be used for effective controlled delivery of the drug directly to the colon [44].…”
Section: Biopolymers and Biopolymer Nanocompositesmentioning
confidence: 99%
“…A controlled release of the drug Dexamethasone from CS was observed once the coating layer of the pH-dependent polymer complex started to dissolve at a higher pH (6.8). It was concluded that the CS nanoparticles coated with PAA-PVP complexes can be used for effective controlled delivery of the drug directly to the colon [44].…”
Section: Biopolymers and Biopolymer Nanocompositesmentioning
confidence: 99%
“…The nanocomposites of chitosan can hold and protect anticancer drugs quite efficiently and effectively. One study showed the development of chitosan nanoparticles loaded with dexamethasone, followed by coating with a pH-dependent interpolymer complex based on poly(acrylic acid)/ poly(vinyl pyrrolidone) polyblends complexes that were very effective when it comes to directed drug delivery to the colon as these coated particles have significantly large protection in simulated gastric fluid [15]. Chitosan-magnetic nanoparticle (CS-MNP)-based carrier system is another carrier system that has been studied quite extensively for cancer treatments in the last few years.…”
Section: Chitosan-based Nanocomposites In Cancer Treatmentsmentioning
confidence: 99%
“…Sabra et al [ 6 ] also proposed chitosan-pectinate nanoparticles for the colon-targeted delivery of curcumin, prepared by the ionic gelation method. In addition, dexamethasone-loaded chitosan microparticles prepared by spray drying presented a potential use as a means of colon-specific drug delivery [ 7 ].…”
Section: Introductionmentioning
confidence: 99%